2012
DOI: 10.1016/j.jacc.2012.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Do Bisphosphonates Slow the Progression of Aortic Stenosis?

Abstract: In this retrospective analysis of older female patients, bisphosphonates do not have a significant impact on the hemodynamic or clinical progression of aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The effect of osteoporosis therapy has been investigated because of an association between aortic valve calcification and low skeletal bone mineral density (Aksoy et al, 2005). Several small observational studies demonstrated a possible link between use of bisphosphonates and slowing of AVS progression (Skolnick et al, 2009;Sterbakova et al, 2010;Innasimuthu and Katz, 2011), although such beneficial effects may be not remarkable in older women (Aksoy et al, 2012). Taken together, prospective randomized clinical studies are certainly needed to evaluate the role of regulation of calcium and phosphate metabolism for preventing progression of CAVD especially at its early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of osteoporosis therapy has been investigated because of an association between aortic valve calcification and low skeletal bone mineral density (Aksoy et al, 2005). Several small observational studies demonstrated a possible link between use of bisphosphonates and slowing of AVS progression (Skolnick et al, 2009;Sterbakova et al, 2010;Innasimuthu and Katz, 2011), although such beneficial effects may be not remarkable in older women (Aksoy et al, 2012). Taken together, prospective randomized clinical studies are certainly needed to evaluate the role of regulation of calcium and phosphate metabolism for preventing progression of CAVD especially at its early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of degenerative aortic valve to AS is a multifactorial and complicated process that differs among individuals with respect to time course. 14 and bisphosphonates, 15 have been administered in attempts to prevent progression of AS. However, none of those trials could prove any significant effects.…”
Section: Can We Predict or Prevent Progression Of Aortic Stenosis?mentioning
confidence: 99%
“…Furthermore, our findings add to the evidence for a reciprocal regulation of bone metabolism and calcification of the aortic valve. It seems less likely that valve calcification is a secondary phenomenon of catabolic bone metabolism resulting in osteoporosis given that for instance bisphosphonate treatment did not have relevant impact on the progression of aortic stenosis in a retrospective analysis [8]. More plausibly, common mechanisms underlie both osteoporosis and calcific aortic disease.…”
mentioning
confidence: 98%